Influence of oxygen on electronic correlation and transport in iron in the Earth’s outer core - Germán G. Blesio; Leonid V. Pourovskii; Markus Aichhorn; Monica Pozzo; Dario Alfè; Jernej Mravlje (Communications Earth & Environment)
Abstract Knowing the transport properties of iron at the Earth’s core conditions is essential for the geophysical modeling of Earth’s magnetic field generation. Besides by extreme pressures and temperatures (which cause scattering by thermal disorder to dominate), transport may be also influenced by the presence of light elements and electron-electron scattering. We used a combination of molecular dynamics, density functional theory, and dynamical mean-field theory methods to examine the impact of oxygen impurities on the electronic correlations and transport in the Earth’s liquid outer core. We find electronic correlations to be moderately enhanced by oxygen admixture. At realistic 10 atomic% of oxygen, the thermal conductivity suppression by electronic correlations (about 20%) is of the same magnitude as that due to oxygen inclusion. Hence, both play an equally important role in reducing the conductivity and stabilizing the geodynamo. We also explain the reduction of Lorenz ratio in core matter.